2013
DOI: 10.1001/jama.2013.277064
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of a Fixed-Dose Combination Strategy on Adherence and Risk Factors in Patients With or at High Risk of CVD

Abstract: for the UMPIRE Collaborative Group IMPORTANCE Most patients with cardiovascular disease (CVD) do not take recommended medications long-term. The use of fixed-dose combinations (FDCs) improves adherence in several clinical areas. Previous trials of cardiovascular FDCs have assessed short-term effects compared with placebo or no treatment. OBJECTIVE To assess whether FDC delivery of aspirin, statin, and 2 blood pressure-lowering agents vs usual care improves long-term adherence to indicated therapy and 2 major C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
278
0
19

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 368 publications
(337 citation statements)
references
References 37 publications
8
278
0
19
Order By: Relevance
“…Three trials were collaboratively planned, conducted and analysed, based on the same protocol, with minor regional adaptations: UMPIRE, 6 with participants from the United Kingdom, Ireland, the Netherlands, and India; Kanyini-GAP conducted in Australia 4 and IMPACT conducted in New Zealand. 5 A prospective IPD meta-analysis was also registered with the Australian New Zealand Clinical Trial Registry: ACTRN12612000980831 with a protocol and pre-specified data analysis plan published.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three trials were collaboratively planned, conducted and analysed, based on the same protocol, with minor regional adaptations: UMPIRE, 6 with participants from the United Kingdom, Ireland, the Netherlands, and India; Kanyini-GAP conducted in Australia 4 and IMPACT conducted in New Zealand. 5 A prospective IPD meta-analysis was also registered with the Australian New Zealand Clinical Trial Registry: ACTRN12612000980831 with a protocol and pre-specified data analysis plan published.…”
Section: Methodsmentioning
confidence: 99%
“…In the largest trial (UMPIRE), self-reported intensive physical activity levels were not reduced, and moderate activity levels were increased. 6 Among the 724 participants taking a more potent statin at baseline (almost all of whom were taking atorvastatin ≥ 20mg or rosuvastatin ≥10mg), allocation to a polypill did not lead to a deterioration in LDL control at 12 months (LDL difference 0.05; -0.05 to 0.14 mmol/l).…”
Section: Additional Safety Analysesmentioning
confidence: 95%
See 1 more Smart Citation
“…More controversial is the use of two drugs to treat the same condition, both of them in lower than recommended doses for effective treatment, in order to avoid adverse drug effects. It should be emphasized that such an approach should be considered very carefully, and an alternative using a single drug may be preferable; however, the use of the so-called poly-pill or multi-pill is an interesting innovation [10].…”
Section: Treatment Of Adverse Drug Effectsmentioning
confidence: 99%
“…Polypills are associated with greater adherence in patients with low baseline adherence compared with patients who already have high adherence. 4 Rather than replace usual care for CVD prevention, polypills will likely be a useful adjunct. …”
mentioning
confidence: 99%